Bond Strength of Fusion Bonded Epoxy-Coated Reinforcement in Concrete - G M Sadiqul Islam; Ehsan Ahmed; Md. Sabbir Hossain; S. M. Sharif Uddin (Journal of the Civil Engineering Forum, 2019)
Fusion-bonded epoxy-coated steel is expected to extend the service life of the reinforced concrete structure in chloride-laden environments. However, the effect of coating on the bond-strength between rebar and concrete is not well understood yet. This research, therefore, studied the effect of epoxy-coating on the bond characteristics of reinforcing bars in concrete. The bond characteristics were assessed through pullout test considering variables viz. concrete strength, embedded length and bar diameter. The load was applied to reinforcing bars embedded in concrete until bond strength between the bar and concrete exceeded. Bond strength of epoxy-coated bars was compared with that of the uncoated bars. It was found that epoxy-coating reduced the bond strength approximately 25% for Ø20mm bar and 12% for Ø16mm and Ø12mm bar. As with uncoated bar, bond strength of coated bars were also increased with concrete strength. However, the bond strength ratio between coated and uncoated bars was found almost independent of concrete strength. Based on the test results, a development length modification factor of 1.33 is proposed for Ø20mm bar and 1.15 for Ø12mm and Ø16mm bar to compensate the bond strength reduction due to the epoxy coating.